Therapeutic Management of Foetal Mummification in a Jersey Crossbred Cow - Kumar Tiwari, Aman; Paduvaralli Thammanna, Swethasri; Arvind Chauhan, Shalaka (The Indian Journal of Animal Reproduction, 2025)
The reported incidence of bovine fetal mummification  is between 0.13-1.8% (Kumar and Saxena, 2018). Higher  incidences are seen in Jersey and Guernsey breeds with  recurrence (30%) in the those having experience of similar event in their previous gestation (Lefebvre, 2015). Fetal  mummification in cattle occurs around 70 days of gesta tion after the stages of placentation and fetal ossification  (Kumar et al., 2018a). However, most commonly reported  cases are between 3rd to 8th months of gestation (Kumar et  al., 2019). Fetal mummies in cattle are covered with a vis cous brown colored sticky material and therefore, termed as  hematic or chocolate mummification (Kumar and Saxena,  2018). Infectious (Leptospirosis, Bovine Viral Diarrhoea  and Neospora caninum infections), non-infectious (uterine  torsion, twisted or compressed umbilical cord, hormonal disturbances and chromosomal aberrations) as well as  environmental conditions (drought and extreme weather)  serve as etiological factors in cattle (Arunpandian et al., 2024). Absence of fetal signal for parturition induction  causes pregnancy to remain undisturbed (Noakes et al., 2019). Resorption of amniotic and allantoic tissues post  foetal death dehydrates the foetal tissues. The longer the  foetus is retained in-utero, the dryer, firmer and leatherier  it becomes.
Keywords: Hematic; Foetal mummification; Jersey Crossbred cow